Assessing built environment walkability using activity-space summary measures - Tribby, Calvin P; Miller, Harvey J; Brown, Barbara B; Werner, Carol M; Smith, Ken R (Journal of Transport and Land Use, 2015)
There is increasing emphasis on active transportation, such as walking, in transportation planning as a sustainable form of mobility and in public health as a means of achieving recommended physical activity and better health outcomes. A research focus is the influence of the built environment on walking, with the ultimate goal of identifying environmental modifications that invite more walking. A key issue is determining the spatial units for walkability measures so that they reflect potential walking behavior. This paper develops methods for assessing walkability within individual activity spaces: the geographic region accessible to an individual during a given walking trip. Based on objective walkability measures of the street blocks, we use three summary measures for walkability within activity spaces: i) the average walkability score across block segments, ii) the standard deviation, and iii) the network autocorrelation. We assess the method using data from an empirical study of built environment walkability and walking behavior in Salt Lake City, Utah. We visualize these activity-space summary measures to compare walkability among individuals’ trips within their neighborhoods. We also compare summary measures for activity spaces versus Census block groups, with the result that they agree less than half of the time.